Market and regulatory headwinds build for MENA gas exporters to Europe - Mostefa A. Ouki (The Oxford Institute for Energy Studies, 2024)
Middle East and North Africa (MENA) gas exporters are facing long-term market and regulatory challenges in Europe. The near three-year continuous decline in Europe's gas demand since the beginning of the Ukraine crisis is a key challenge for these exporters who are concerned about whether this fall in gas consumption is a structural market transformation that will result in a significant shrinking of Europe's gas market. MENA's natural gas exporters to Europe, along with other gas exporters from other regions, will also be facing the impact of new EU green regulations. Although these regulations will have a long-term impact and are likely to affect some MENA exporters more than others, they are still a source of concern for MENA's hydrocarbon exporters. This paper examines the outlook for MENA's main natural gas exporters to Europe, namely Algeria, Libya, Egypt (a net exporter until recently), and Qatar, and identifies both the market and regulatory challenges ahead. The context and conclusions of this paper apply not only to the main existing MENA gas exporters to Europe, but also to other potential MENA gas exporters, especially those located in the Gulf Cooperation Council subregion.
Keywords: 330; decarbonisation; EU green regulations; Europe; Gas Markets; LNG; methane emission reduction; Middle East; North Africa; Pipeline gas